Fiscal and monetary policy interactions in a developing economy: A DSGE-based evidence from Nigeria - Queen E. Oye; Philip Alege (CBN Journal of Applied Statistics, 2022)
This study characterizes the nature of fiscal-monetary interaction in Nigeria and gauges its macroeconomic effects by estimating a New Keynesian Dynamic Stochastic General Equilibrium (NK DSGE) model. Two policy simulations were also conducted. The first experiment considers the desirable active-passive policy mix while the second experiment ranks alternative monetary policy rules among the differing objectives of price, output and exchange rate stabilization. The study finds that fiscal and monetary policies interact as complements in an active monetary and passive fiscal policy mix over the sample period. The result from the first policy simulation reveals that the active monetary and passive fiscal stance guaranteed the least volatile macroeconomic outcomes. The result from the second experiment shows that the monetary authority in Nigeria should maintain its focus on conventional mandate of price stabilization to induce improved output and welfare gains. This implies that the existence of an independent central bank that can control inflation without being constrained by fiscal decision is desirable.
Keywords: C69; E61; E63; 330; DSGE model; fiscal policy; monetary policy; policy interaction